Analyzing the cross-national comparability of party positions on the socio-cultural and EU dimensions in Europe. Issue 2 (17th April 2022) - Bakker, Ryan; Jolly, Seth; Polk, Jonathan
Abstract: Using survey vignettes and scaling techniques, we estimate common socio-cultural and European integration dimensions for political parties across the member states of the European Union. Previous research shows that party placements on the economic left-right dimension are cross-nationally comparable across the EU; however, the socio-cultural dimension is more complex, with different issues forming the core of the dimension in different countries. The 2014 wave of the Chapel Hill Expert Survey included anchoring vignettes which we use as "bridge votes" to place parties from different countries on a common liberal/authoritarian dimension and a separate common scale for European integration. We estimate the dimensions using the Bayesian Aldrich–McKelvey technique. The resulting scales offer cross-nationally comparable, interval-level measures of a party's socio-cultural and EU ideological positions.